Plasma transfusion practice in adult surgical patients: systematic review of the literature - Adam, Elisabeth; Fischer, Dania (Transfusion medicine and hemotherapy, 2020)
Background:Plasma transfusions are most commonly used therapeutically for bleeding or prophylactically in non-bleeding patients prior to invasive procedures or surgery. Although plasma transfusions generally seem to decline, plasma usage for indications that lack evidence of efficacy prevail.Summary:There is wide international, interinstitutional, and interindividual variance regarding the compliance with guidelines based on published references, supported by appropriate testing. There is furthermore a profound lack of evidence from randomized controlled trials comparing the effect of plasma transfusion with that of other therapeutic interventions for most indications, including massive bleeding. The expected benefit of a plasma transfusion needs to be balanced carefully against the associated risk of adverse events. In light of the heterogeneous nature of bleeding conditions and their rapid evolvement over time, fibrinogen and factor concentrate therapy, directed at specific phases of coagulation identified by alternative laboratory assays, may offer advantages over conventional blood product ratio-driven resuscitation. However, their outcome benefit has not been demonstrated in well-powered prospective trials. This systematic review will detail the current evidence base for plasma transfusion in adult surgical patients.